Growth Response of Gyrinops verstegii Cuttings on Various Concentration Level of IBA (Indole Butyric Acid) Hormone RESPON PERTUMBUHAN STEK Gyrinops verstegii TERHADAP PEMBERIAN BERBAGAI TINGKAT KONSENTRASI HORMON IBA (Indole Butyric Acid) - Amilda Auri; Petrus A. Dimara (Jurnal Silvikultur Tropika, 2016)
Until now, the supply of the seed sources still rely on seeds or germs. Meanwhie, the certain wood species, the production of seeds are insufficient and the handling is quite difficult. Consequently, when seedling, their germination capacities and growth percentages are very low. Providing seed source through shoot cuttings which if it is planted in advantegous condition for regeneration, it will grow and develop into fast growing species as well as good quality species. Supplying of plant growth regulator is expectedly able to affect the plant growth when given according to the plant needs. This research aimed to determine the concetration level of growth reglator IBA (Indole Butyric Acid) for the growth of shoot cuttings of agarwood Gyrinops verstegii. The method used in this research is experiment with completely-randomized design (CRD). Results showed that the concentration level of IBA affected the growth of callus, roots and shoots. IBA treatment at the concentration of 300 ppm showed the best response to the cutting life, growed earlier, the number and the length of shoot are greater. However, in the root zone, the treatment without IBA hormone provided better response which is showed by the number and the length of root.Key words: Gyrinops verstegii, Indole Butyric Acid, growth response